Cardiac-Derived Extracellular Matrix Enhances Cardiogenic Properties of Human Cardiac Progenitor Cells. Issue 9 (September 2016) - Gaetani, Roberto; Yin, Christopher; Srikumar, Neha; Braden, Rebecca; Doevendans, Pieter A.; Sluijter, Joost P. G.; Christman, Karen L.
The use of biomaterials has been demonstrated as a viable strategy to promote cell survival and cardiac repair. However, limitations on combinational cell–biomaterial therapies exist, as cellular behavior is influenced by the microenvironment and physical characteristics of the material. Among the different scaffolds employed for cardiac tissue engineering, a myocardial matrix hydrogel has been shown to promote cardiogenesis in murine cardiac progenitor cells (mCPCs) in vitro. In this study, we investigated the influence of the hydrogel on Sca-1-like human fetal and adult CPCs (fCPCs and aCPCs) when encapsulated in three-dimensional (3D) material in vitro. fCPCs encapsulated in the myocardial matrix showed an increase in the gene expression level of cardiac markers GATA-4 and MLC2v and the vascular marker vascular endothelial growth factor receptor 2 (VEGFR2) after 4 days in culture, and a significant increase in GATA-4 up to 1 week. Increased gene expression levels of Nkx2.5, MEF2c, VEGFR2, and CD31 were also observed when aCPCs were cultured in the matrix compared to collagen. Cell survival was sustained in both hydrogels up to 1 week in culture with the myocardial matrix capable of enhancing the expression of the proliferation marker Ki-67 after 4 days in culture. When encapsulated CPCs were treated with H2 O2, an improved survival of the cells cultured in the myocardial matrix was observed. Finally, we evaluated the use of the myocardial matrix as hydrogel for in vivo cell transplantation and demonstrated that the gelation properties of the hydrogel are not influenced by the cells. In summary, we showed that the myocardial matrix hydrogel promotes human CPC cardiogenic potential, proliferation, and survival and is a favorable hydrogel for 3D in vitro culture. Furthermore, we demonstrated the in vivo applicability of the matrix as a potential vehicle for cell transplantation.